Viewpoint: “Underutilisation of novel antiplatelet agents – myths, generics, and economics” - Serebruany, Victor L.; Fortmann, Seth D. (Thrombosis and Haemostasis, 2014)
Two oral antiplatelet agents have been recently introduced for acute coronary syndromes indication providing alternatives for dual therapy with aspirin and clopidogrel. In fact, worldwide prasugrel has been on the market for four years, and ticagrelor for over two years. Despite declared benefits over clopidogrel, including hypothetical cost saving advantages, in real life, the clinical utilisation of both agents is small. Generic clopidogrel, and price differences are claimed as major obstacles to prevent broader prasugrel and ticagrelor use. However, these economic difficulties are barely supported by available evidence, and served mostly to protect questionable management spending, as an exuse to explain why in reality cardiologists are so sceptical about both novel agents, and to convince the sharehoders that their money is not wasted, misleading the owners with regard to future success. Importantly, brand Plavix® is used worldwide 5–10 times more often than new agents, despite heavy generic competition. The future of prasugrel outside Japan, where much lower reasonable dose will be used is not impressive due to lack of further outcome studies, negative results of the latest trials, and less than four years left before patent expiration. The fate of ticagrelor will depend on verification of deaths numbers in the ongoing United States Department of Justice PLATO investigation, and confirmation of the mortality benefit in the PEGASUS TIMI-54 trial.
Keywords: Ticagrelor; prasugrel; clopidogrel; generics; clinical utilisation